EFFICIENCY FRONTIERS FOR DECISION OPERATORS - Raffo Lecca, Eduardo (2005)
This work highlights the Data Envelopment Analysis (DEA) Methodology as a benchmarking tool suitable to quantify or measure the efficiency of an organization. From basic concepts to efficiency frontier functions are explained here, showing the mathematical fundamentals, together with the DEA goodness and scope.